2018
DOI: 10.1155/2018/8391830
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Moisture and Electrical Conductivity in Clay Liners

Abstract: This research is aimed at investigating the influence of ambient air temperature on the moisture content and electrical conductivity of clay sand mixtures. Volume changes as a result of shrinking or swelling are very much related to the moisture content and the electrical conductivity for liners consisting of sand and clays. The laboratory tests carried out for clay sand mixtures subjected to drying indicated a bilinear trend for 15, 20, 25, and 30% clay content. Moisture content measurements are influenced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…For low temperature (8 °C ≤ T ≤72 °C), significant electrical conductivity (σ = 1.45 10 −6 Ω −1 m −1 ) for TM clay was observed, whereas a significant conductivity response (σ = 1.6910 −6 Ω −1 m −1 ) for RM sample as found for high temperature (72 °C ≤ T ≤ 140 °C). Higher electrical conductivity is associated with moisture content and saturation of clay, and this is presented by many researchers [37]. However, there are many parameters that can affect the measurement of the electric conductivity such as clay texture, porosity, particle-size distribution, mineralogical composition, form and distribution of water in clay, salt content, charge carriers and temperature.…”
Section: Characterization Of the Powdermentioning
confidence: 99%
“…For low temperature (8 °C ≤ T ≤72 °C), significant electrical conductivity (σ = 1.45 10 −6 Ω −1 m −1 ) for TM clay was observed, whereas a significant conductivity response (σ = 1.6910 −6 Ω −1 m −1 ) for RM sample as found for high temperature (72 °C ≤ T ≤ 140 °C). Higher electrical conductivity is associated with moisture content and saturation of clay, and this is presented by many researchers [37]. However, there are many parameters that can affect the measurement of the electric conductivity such as clay texture, porosity, particle-size distribution, mineralogical composition, form and distribution of water in clay, salt content, charge carriers and temperature.…”
Section: Characterization Of the Powdermentioning
confidence: 99%
“…In fact, the suitability and advantages of some man-made clay liners with kaolin-bentonite (K-B) or kaolin-sand (K-S) mixtures with different compositions have been reported in some research [13,17]. ey have shown that the additions of kaolin and sand will reduce the swelling capacity and improve the mechanical behaviour of the liner system [14,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%